1980
DOI: 10.1002/jcp.1041050107
|View full text |Cite
|
Sign up to set email alerts
|

Cell density and amino acid transport in 3T3, SV3T3, and SV3T3 revertant cells

Abstract: The transport of selected neutral and cationic amino acids has been studied in Balb/c 3T3, SV3T3, and SV3T3 revertant cell lines. After properly timed preincubations to control the size of internal amino acid pools, the activity of systems A, ASC, L, and Ly+ has been discriminated by measurements of amino acid uptake (initial entry rate) in the presence and absence of sodium and of transport-specific model substrates. L-Proline, 2-aminoisobutyric acid, and glycine were primarily taken up by system A; L-alanine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
19
1

Year Published

1981
1981
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 39 publications
3
19
1
Order By: Relevance
“…AAT expression is also related to the cancer microenvironment in interesting ways. Intratumoral cell density generally increases with tumor progression, and the transport activity of system ASC, but not of system L, decreases with increasing cell density [38]. We recently demonstrated that [ 18 F]fluciclovine accumulation is positively correlated with cell density in a rat glioma model [39].…”
Section: Discussionmentioning
confidence: 99%
“…AAT expression is also related to the cancer microenvironment in interesting ways. Intratumoral cell density generally increases with tumor progression, and the transport activity of system ASC, but not of system L, decreases with increasing cell density [38]. We recently demonstrated that [ 18 F]fluciclovine accumulation is positively correlated with cell density in a rat glioma model [39].…”
Section: Discussionmentioning
confidence: 99%
“…The induced synthesis of stress proteins by the cells under these conditions has been monitored in terms of the presence of mRNA for HSP70, the pattern of polypeptides synthesised, and the accumulation of HSP70 detectable by monoclonal antibodies. (Borghetti et al, 1980). These cells were routinely kept in culture for up to 2 months and discarded; then fresh cultures were started again from frozen stocks.…”
mentioning
confidence: 99%
“…A similar decrease has been reported by Lever (1982) when measuring a-aminoisobutyric acid transport. This behaviour is reminiscent of that described in other cells in culture (Guidotti et al, 1978;Borghetti et al, 1980) where a marked decrease in amino acid transport activity was observed as cell density increased. This phenomenon has been interpreted in terms of the coordinated regulation of cell growth, supporting the view that nutrient uptake might play an important role in the regulation of cell growth.…”
mentioning
confidence: 56%
“…At least two explanations could account for the uneven distribution of alanine uptake observed here. The first one is based on the observation by Borghetti et al (1980) showing that the activity of system A is modulated so that it is low when high cell density is attained by 3T3Balb C fibroblasts in culture. A similar observation has been reported by Boerner and Saier (1982) for MDCK cells; this is an epithelial cell line derived from canine kidney that retains several characteristics of distal tubular epithelium.…”
Section: Discussionmentioning
confidence: 99%